The Influence of Think-Pair-Share Technique on Students’ Reading Comprehension at Junior High School - Hamzah Hamzah; Fajriani Fajriani (Institut Agama Islam Negeri Palopo, 2022)
The objectives of the research were to find out the influence of Think-Pair-Share Technique on Students Reading Comprehension at SMPS PPM Al-Ikhlas Lampoko and to find out significant difference students reading comprehension achievement between post-test class experiment and post-test class control at SMPS PPM Al-Ikhlas Lampoko. The method of the research was quantitative method and type of the research quasi-experimental one group pre- test and posttest design. The sampling used was simple random technique. The total number of populations was 135 students and total number of samples was 38 students. The instrument of the research was test. The results showed that: (1) There is an influence of Think-Pair-Share technique on students reading comprehension in narrative text at SMPS PPM Al-Ikhlas Lampoko. Where students reading comprehension taught used Think-Pair-Share technique was increased. (2) There is significant difference students reading comprehension achievement between Think-Pair-Share technique and Expository way at SMPS PPM Al-Ikhlas Lampoko. Where the mean of posttest class experiment was higher than posttest class control